Laparoscopic Heller myotomy after multiple endoscopic injections and dilations: a case report - Mahfouz, Mohammad Eid M. (International Surgery Journal, 2024)
Achalasia is a primary esophageal disease that affects the esophagus and lower esophageal sphincter (LES). Many medications have been used for achalasia. However, adverse reactions and a prevailing absence of potency have been reported with these therapies. The best management leads to disturbing LES with endoscopic dilation or surgically. This is a 58-year-old woman with a 25-year history of achalasia who has experienced laparoscopic Heller myotomy (LHM) with Toupet fundoplication due to persistent symptoms despite previous endoscopic interventions. The procedure successfully addressed thickened LES muscle layers and achieved positive postoperative results, with the patient's Eckardt score dropping from >9 to <3. LHM with Toupet fundoplication proved its effectiveness in managing refractory type III achalasia. Despite concerns about postoperative reflux, the procedure offered substantial relief. Ongoing research will refine the balance between invasiveness and efficacy in such conditions.